The impact of tax on new product launches. (December 2022) - Kang, Yaling; Wu, Zhiqiao; Qin, Hengle
Highlights: We investigate the conflict objectives between HQ and R&D caused by asymmetric information. The response to tax differences is distorted under the decentralized structure. Gap between OEM and R&D occurs when the penalty cost is relatively high. Abstract: Research and development (R&D) divisions are important in the tax planning of multinational firms (MNFs), many of which have formed multinational supply chains involving overseas design of new technology and domestic production of new products. This study investigates the phenomenon of conflicting objectives between MNF headquarters and R&D caused by asymmetric information, and we present a coordination contract to eliminate this contradiction by introducing penalty costs. Under a random R&D design success time and decreasing market demand over time, we first explore the optimal component preparation time and optimal design success prediction time. In a decentralized structure, we find that R&D can meet the time expectation of headquarter only when the associated penalty cost is relatively low—that is, coordination between headquarters and R&D can be realized. Moreover, tax differences can significantly affect the proposed threshold for penalty costs, which then distort the behavior of a decentralized structure, resulting in conflicting objectives and reducing loss in multinational supply chains. Finally, we re-examine the robustness of our conclusions and find that all hold in terms of tax asymmetric treatment of profits and losses or relaxing the failure rate assumption.